Optimization of actuating torques in multi-bar prosthetic joints with springs. Issue 7 (3rd July 2017) - Sun, Yuanxi; Ge, Wenjie; Zheng, Jia; Xia, Fan; Dong, Dianbiao
ABSTRACT: This article presents the optimization of actuating torques in multi-bar prosthetic joints with springs. First, a general model of the planar multi-bar single-loop mechanism with springs for the prosthetic joint is proposed. Secondly, the dynamic matrix of the mechanism is solved by analysing the force condition of a single bar, with the external forces and torques, the forces and torques of the springs as well as the actuating torques being considered. Thirdly, a general optimization method of actuating torques is proposed by taking into account different spring installation situations. Finally, two prosthetic joint examples are presented to show the detailed optimization process, and the effectiveness of the proposed optimization is verified by simulation and experiment. The results prove that the addition of springs in multi-bar prosthetic joints can reduce the absolute values and fluctuations of actuating torques, leading to better energy saving.